Mental Health Program Effectiveness and Experiences of Philippine Local Government-Funded Colleges: Basis for Mental Health Program Advancement - Ebro, Eric Ds (Universitas Djuanda, 2025)
The study discussed and examined the efficacy of mental health initiatives in selected local government-funded institutions in Zambales. It used a mixed-method research design. Sixty rank-and-file employees of local government-funded colleges served as the study's participants. The quantitative and qualitative data were gathered through a survey with closed-ended and open-ended questions. The research instrument was validated by public administration and public health experts and was pilot-tested. Results show that the mental health programs among local government-funded colleges are effective, as shown in the composite weighted mean of 2.97 (SD=0.52). The experiences of the rank-and-file were reflected in research themes such as empowered workers, efficient implementation, and unseemly behavior. The output of the study is an intervention program that centers on budget allocation, scheduling free health consultations, fostering partnerships, and conducting program evaluations.